Designing with Natural Materials - A. Ormondroyd, Graham; F. Morris, Angela; Taylor and Francis (Boca Raton, FL : CRC Press, 2018)
In a world now forced to address the issues of sustainability, environmental impact, and the widespread pollution of land and oceans with manmade materials, alternative resources must be considered for the future of the planet. A vast array of natural materials is available throughout the world with properties that are often superior to the man-made alternatives. Designing with Natural Materials fills the gap between the current scientific knowledge of the use of natural materials and product design and acts as a bridge between the two disciplines. The book serves as an introduction to natural materials within the context of design. The chapters include case studies, research, and a historical perspective. It develops ideas of designing with natural materials in specific areas and looks to the future of new biobased materials and how these will influence design. The work offers insight to designers of biobased materials across a range of different design disciplines while also providing insights to scientists on the process of design, production, and the needs of a material beyond those traditionally analyzed in the laboratory. The final chapters touch on the use of bioinspiration and biomimicry in the development and use of biobased materials and how natural design will influence both material design and products in the future. The book will be of interest to engineers, scientific researchers, professional designers, students, those working in industry who are considering using natural materials as an alternative to current unsustainable options, and anyone who has an interest in the subject. It features the following.
1. An Introduction to the Aesthetics of Design -- --[Bruce Wood] -- 2. Selection of Natural Materials Using CES EduPack -- --[Martin. P. Ansell] -- 3. Natural Materials Composition and Combinations -- --[Morwenna Spear] -- 4. Designing with the Life Cycle in Mind -- --[C. Skinner] -- 5. Restoring Credibility to Natural Materials -- --[D. K. Spilsbury] -- 6. Natural Materials in Automotive Design -- --[Kerry Kerwan and Stewart Coles] -- 7. Rediscovering Natural Materials in Packaging -- --[Angela F. Morris] -- 8. Designing Tall Buildings with Natural Materials -- --[Richard Harris and Wen-Shao Chang] -- 9. Emerging Nature Based Materials and Their Use in New Products -- --[Morwenna Spear] -- 10. Bio-Inspired Design Enhancing Natural Materials -- --[Chris Holland]
Includes bibliographical references and index.
Also available in print format.
Keywords: Product design; New products -- Materials; TECHNOLOGY & ENGINEERING / Mechanical; TECHNOLOGY & ENGINEERING / Material Science; biobased materials; biomaterials; biomimetic materials; green materials; natural materials; sustainable materials; Electronic books